2018
DOI: 10.1039/c8ra00290h
|View full text |Cite
|
Sign up to set email alerts
|

Boron-doped graphene as a metal-free catalyst for gas-phase oxidation of benzyl alcohol to benzaldehyde

Abstract: Boron doped graphene for the oxidative dehydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…Figure 1 shows the XRD patterns of catalysts including graphene (G), ferrous oxide (Fe), ferrous oxide doped with graphene (FG), ferrous oxide doped with aluminum (FA), and FAG made from GO, aluminum nitrate, ferric nitrate, and alcohol (Table 2). Pattern (a) shows two broad diffraction peaks at 24.6° (d = 0.34 nm) and 43.0° (d = 0.21 nm) for G. Cheng et al [26] reported an intense and sharp reflection centered at 11° for GO, corresponding to a c-axis interlayer spacing of 0.81 nm [25]. The characteristic peak of GO disappeared since it underwent thermal processing in Ar atmosphere at 1173 K for 2 h, confirming that most of the oxygen-containing functional groups in GO were detached under the supercritical condition with high temperature and high pressure.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the XRD patterns of catalysts including graphene (G), ferrous oxide (Fe), ferrous oxide doped with graphene (FG), ferrous oxide doped with aluminum (FA), and FAG made from GO, aluminum nitrate, ferric nitrate, and alcohol (Table 2). Pattern (a) shows two broad diffraction peaks at 24.6° (d = 0.34 nm) and 43.0° (d = 0.21 nm) for G. Cheng et al [26] reported an intense and sharp reflection centered at 11° for GO, corresponding to a c-axis interlayer spacing of 0.81 nm [25]. The characteristic peak of GO disappeared since it underwent thermal processing in Ar atmosphere at 1173 K for 2 h, confirming that most of the oxygen-containing functional groups in GO were detached under the supercritical condition with high temperature and high pressure.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…Dynamic study shows that when nitrogen-doped graphene is used as a catalyst, the activation energy of reaction is 56.1 kJ mol −1 , close to one of the traditional noble metal loaded catalyst, 51.4 kJ mol −1 . Cheng et al [26] used boron-doped graphene as a metal-free catalyst in the gasphase oxidation of BA to BD and achieved excellent performance with selectivity of BD of up to 99.2%.…”
Section: Introductionmentioning
confidence: 99%
“…3). The peak at 192.5 eV in insensitive lines without B treatment was most likely from B-N and B-C bonds [19,[41][42][43], which indicated that the insensitive lines had incorporated the B into tissues. The observation that insensitive lines incorporated more B directly into root tissues than sensitive lines may be a factor in the reduced susceptibility of insensitive lines to the development of clubroot symptoms.…”
Section: Boron K-edge Xanes Analysismentioning
confidence: 99%
“…XPS results indicated that the graphitic sp 2 B species (BC 3 ) is the mainly boron dopant species incorporated in the graphene lattice, which could significantly improve the content of the active ketone carbonyl groups (C=O) of catalytic reaction on the graphene and thus lead to significantly improved catalytic activity. As a result, compared to the un‐doped graphene, the conversion of benzyl alcohol over BGs increased 2.35 times and the selectivity of benzaldehyde increased from 77.3 % to 99.2 % . A N‐, O‐, and S‐tridoped nanoporous carbons (NOSCs) have been synthesized via polymerization of pyrrole using (NH 4 ) 2 S 2 O 8 as oxidant by the hard template method.…”
Section: Oxidationmentioning
confidence: 99%
“…As a result, compared to the un-doped graphene, the conversion of benzyl alcohol over BGs increased 2.35 times and the selectivity of benzaldehyde increased from 77.3 % to 99.2 %. [65] A N-, O-, and S-tridoped nanoporous carbons (NOSCs) have been synthesized via polymerization of pyrrole using (NH 4 ) 2 S 2 O 8 as oxidant by the hard template method. In this work, the authors mainly focused on their catalytic activity toward ORR.…”
Section: Alcohols Oxidationmentioning
confidence: 99%